Student Motivation in Learning Sports and Health Physical Education At SLBN 033 Tembilahan* - rahmawati, gusti; indra putra, edi susrianto (Jurnal Olahraga Indragiri, 2023)
The problem of this research is to find out how students are motivated in learning physical education, sports and health at SLBN 033 Tembialahan. This type of research is descriptive. When the research was carried out in September 2022. The place of research was SLBN 033 Tembilahan. The sample collection technique used in this study was "total sampling" which amounted to 14 people. The instrument used to collect data is a questionnaire or questionnaire using a guttman scale. Data were analyzed using the frequency distribution formula in the form of a percentage. From the results of the research, the intrinsic factor sub-variable was 67.65% and the extrinsic factor was 69.23% so that the motivation of students in learning sports and health physical education at SLBN 033 Tembilahan was 68.33% which was high because it was located at intervals of 51% -100%. So it can be concluded that the two sub-variables of intrinsic factors and extrinsic factors have an effect on students' motivation in learning sports and health physical education at SLBN 033 Tembilahan./69**